Perancangan Produk Obstacle Skateboard Pemula Melalui Pendekatan Design Thinking Pada Karakteristik Pengguna - muhammad zaidan naufal pratama; Sulistyo Setiawan (Penerbit Itenas, 2024)
The idea and design of Sk8forfun Obstacle Kit, an obstacle skate product for beginners that meets the needs of inexperienced skaters, is demonstrated in this study. Children and teenagers are becoming increasingly interested in skateboarding, which has increased the demand for accessible and safe training equipment. There is a considerable need in the market for products made with beginners in mind as most of the current products are aimed at experienced skaters. Jumpers and low rails make up the main part of the Sk8forfun Obstacle Kit. Each obstacle has been designed to be safe, comfortable and easy to use. Users of different ages and ability levels can use the skateboard obstacle due to its height-adjustable feature. Using qualified materials for its manufacture. Non-slip coating and galvanized steel construction ensure longevity and user safety. To increase stability and reduce the risk of injury, each component has rounded edges and a solid base. Material selection, dimensional suitability, and modular construction for easy transportation and storage were important design factors. Each obstacle course has been designed with ergonomics in mind, supporting the user's natural posture and movement to lower the chance of injury and enhance learning. Clear usage guidelines and safety advice are included with the product. This report describes the design philosophy behind the product, target users, as well as the safety and ergonomic aspects that set it apart from competing products, Sk8forfun Obstacle Kit seeks to encourage more people to skateboard while guaranteeing their comfort and safety by creating a supportive and confidence-building environment for beginners. By meeting the unique needs of inexperienced skaters, this product not only closes a significant market gap, but also advances the expansion and diversity of the skating community.